(untitled) (Movimenta (ISSN 1984-4298), 2022)
Introduction: According to the World Health Organization (WHO), spinal disorders affect approximately 80% of the population at some point in their lives. Individuals affected by these conditions are frequent users of health services. This aspect causes an increase in health demand and, consequently, in the direct costs arising from care. In this sense, understanding the sociodemographic characteristics of individuals affected by this condition can help in planning goals and organizing services. Objective: To characterize a population of individuals with spinal disorders treated at the outpatient clinic of a large hospital in the Federal District, in 2018. Method: Cross-sectional study approved by CEP/FEPECS (26011419.7.3001.5553), comprising individuals with chronic disorders in the column. Data were descriptively analyzed using mean and standard deviation, relative and absolute frequencies. Results: 200 electronic medical records were analyzed. It was found that the majority of participants were female (75%), married (31%), service workers and commerce sellers (27%) and sedentary (51%). Mean age was 52 years (SD: 15). Among the most frequent comorbidities, Systemic Arterial Hypertension (45%) and Depression (22.5%) stood out. It was observed that the most frequent spinal disorder was low back pain (84%). Conclusion: Our findings demonstrate that individuals with spinal disorders seen at the outpatient clinic investigated were mostly women aged between 40 and 60 years, sedentary and with the presence of comorbidities. Low back pain was the most prevalent condition.